Membangun Kreativitas dan Minat Baca Puisi Melalui Musikalisasi Puisi pada Siswa SMA Muhammadiyah 1 Pekanbaru - Qori Islami Aris; Essy Syam; Yessi Ratna Sari (BIDIK: Jurnal Pengabdian kepada Masyarakat, 2023)
This service activity aims to stimulate students' interest in reading poetry at SMA Muhammadiyah I Pekanbaru through a poetry musicalisation approach. The service team conducted a situational analysis of the partners and found that the students' interest in reading poetry was low due to the lack of understanding and appreciation of poetry and the lack of students' creativity in presenting poetry. This service activity was also carried out as an effort to develop students' creativity in arts and culture. Creativity can help students develop critical and creative thinking skills, problem solving and innovation in various fields. Poetry musicalisation was chosen as a method in this activity because it can increase the appreciation and understanding of literary works, especially poetry. Poetry musicalisation can make poetry more interesting and easier for students to understand, and improve students' language and artistic skills. This method is effective in increasing the appreciation of poetry and helping students to develop their creative skills.